Mendedah Identitas Aktivis Dakwah Kampus dalam Keragaman Keanggotaan LDK-MPM IAIN Sultan Amai Gorontalo - Abdul, Moh. Rivaldi (Jurnal Moderasi, 2021)
This article elaborates on the way in which the identity of campus da’wa activists forms a culture of diversity through Lembaga Dakwah Kampus Mahasiswa Pencinta Mushola (LDK-MPM) in IAIN Sultan Amai Gorontalo. The members of the LDK consist of students from various backgrounds, including PMII, HMI, IMM, KAMMI, etc.  The method used in this study is participant-observation with self/identity theory proposed by Gabriele Marranci as the framework of analysis. This article shows that LDK-MPM since its foundation have been an open organization for all Muslims students regardless of their organizational affiliations. The environments and experiences of those students are diverse, leading to diversity in deciding the organizational affiliations outside of the LDK. The diversity of its members is maintained through the mutual agreement between the members and the murabbi, that LDK is a neutral space for all students. Additionally, they are capable of positions themselves; when to behave as the members of LDK and when to act as the cadre of other extra-campus organizations. LDK-MPM has been a unifying space for Muslims student in IAIN Sultan Amai Gorontalo.